All we need to know about the provisional measures of the international court of justice in allegations of genocide (Ukraine v Russian Federation), but the media reports inaccurately - Gapsa, Miłosz (Vilnius University Open Series, 2023)
On 27 February 2022, Ukraine filed the application instituting proceedings against Russia before the International Court of Justice to obtain provisional measures protecting its rights. It resulted from Russia‘s launch of the “special military operation” against Ukraine on 24 February 2022, in response to the alleged genocide of Donbass communities by the Kyiv regime. The Courted delivered its Order on 16 Marco 2022 and indicated provisional measures. Unfortunately, the Polish media coverage distorted the content of the Order. This article aims to present how the Order was covered and to demystify its content.